Sebastian [videorecording (DVD)] - Mäkelä, Mikko; Mäkelä, Mikko; Mollica, Ruaridh; Quasem, Hiftu; Hyde, Jonathan, 1948-; Ingvar Sigurðsson, 1963-; Brady, Dylan (Kino Lorber, 2024)
"Follows Max, a 25-year-old freelance writer and aspiring novelist who seems well on his way to success in London's cultural spheres. Yet by night, he finds a different kind of exhilaration as a sex worker with the pseudonym Sebastian, meeting men via an escorting platform. Max uses his experiences as Sebastian to fuel his stories, and the worthy debut novel that he has been longing to write finally seems within reach. As Max increasingly struggles to remain in control of a delicately balanced double-life, he must reckon with whether Sebastian is merely a writer's tool in their quest for the ultimate sense of first-hand authenticity--or whether something more is at stake"--